Design & develop automatic battery cyclic tester - Zulfadhli, Sohok (2012)
Environmental concern due to fuel combustion from conventional automobile vehicles has lead to the development of Hybrid Electric Vehicle (HEV). Crucial part of Electric Vehicles (EV) is the battery life that presently limiting the realization of economically viable EV since the battery provides power to the EV. In EV and HEV, the power battery must capable of performing charge and discharge for longer period of time implies that longer life cycle of the battery. Hence, batteries are required to undergo cyclic battery test. However, the cyclic test is time consuming that will result in long waiting time for the test to complete. In addition of conventional battery cyclic test, it costs great expense for battery manufacturer to verify battery life cycle. Each of battery produced under same factory doesn’t mean that all battery performance for particular application is all the same. Chemical reaction in each battery are varies thus affecting the battery performance. Thus, the need for fully automated cyclic test station is appear. Therefore in this project will focus on the design and development of automation of battery cyclic tester. Microsoft Visual Basic will be used to enable automatic battery testing. As proposed, the result from this project is expected to reduce man-hour waiting time during conducting battery testing.